First convert the feet to inches:
3 feet= 36 in.; 4 feet=48 in.
Make an equation for each one:
Type A: h=36+15x
Type B: h=48+10x
Since the questions wants the heights to be equal, h=h so you can substitute so you have:
36+15x=48+10x
5x=12
x=2 2/5 years or 2.4 years
Answer:
The slope is
Step-by-step explanation:
The picture of the question in the attached figure
Let
x ----> the number of days
y ---> the number of tickets sold
we have the points
(1,30) and (7,55)
The formula to calculate the slope between two points is equal to
substitute the given values in the formula
7) 12, 7, 2, -3,...
Answer:
Let's find the recursive formula, explicit formula, and the indicated term for the given arithmetic sequences.
Sequence 1: 1, 4, 1, 10, ...
To find the recursive formula, we need to identify the pattern between consecutive terms. Looking at the sequence, we can see that each term alternates between adding 3 and subtracting 3.
Recursive formula:
a1 = 1 (the first term)
an = an-1 + (-1)^(n+1) * 3
For example, to find the 4th term (a4) using the recursive formula:
a1 = 1 (the first term)
a2 = a1 + (-1)^(2+1) * 3 = 1 + (-1) * 3 = -2
a3 = a2 + (-1)^(3+1) * 3 = -2 + 1 * 3 = 1
a4 = a3 + (-1)^(4+1) * 3 = 1 + (-1) * 3 = -2
Explicit formula:
To find the explicit formula, we need to identify the common difference. In this case, since the terms alternate between adding 3 and subtracting 3, the common difference is not constant.
Indicated term:
To find the indicated term, we need to know which term is being referred to. Please provide the term number or the position of the term in the sequence so that I can assist you further.
-----------------------------------------------------------
Sequence 2: 12, 7, 2, -3, ...
To find the recursive formula, we need to identify the pattern between consecutive terms. Looking at the sequence, we can see that each term decreases by 5.
Recursive formula:
a1 = 12 (the first term)
an = an-1 - 5
For example, to find the 4th term (a4) using the recursive formula:
a1 = 12 (the first term)
a2 = a1 - 5 = 12 - 5 = 7
a3 = a2 - 5 = 7 - 5 = 2
a4 = a3 - 5 = 2 - 5 = -3
Explicit formula:
To find the explicit formula, we need to identify the common difference. In this case, the common difference is -5.
Explicit formula:
an = 12 + (n - 1)(-5)
Indicated term:
To find the indicated term, we need to know which term is being referred to. Please provide the term number or the position of the term in the sequence so that I can assist you further.
Please provide the term number or the position of the term in the sequence so that I can help you find the indicated term.
Step-by-step explanation: